An analysis of the role of communities in care systems co-created with older people. Issue 12 (1st December 2020) - Zuniga, Martin; Salaberria, Eva; Arrieta, Felix
ABSTRACT: The aim of this article is to present the main findings on the role of communities in care provision obtained during a community co-creation process which took place in a neighborhood of the city of Donostia/San Sebastián (Spain). The article is divided into four sections. We first introduce the co-creation concept and its potential as a political strategy. Secondly, we briefly describe the project, its objectives, and the methodology followed. Thirdly, we analyse the main findings obtained from the process and, finally, we discuss the process of co-creation developed by communities and their role in the care of older people.